School directors and management in education - Srdić, Vesna M (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2015)
The main features of school management and organization comprise planning, decision making, management, leadership and communication. Research suggests that successful school management requires not only advanced managerial but also leadership skills, with highly developed social skills as the main competence. In a complex social system, good leadership becomes a fundamental component of a successful organization or institution. Although leadership has for a long time been of interest for theoreticians and practitioners alike, there are still numerous questions waiting to be answered in the area of management and leadership in education. According to the Law on the Basis of Educational System, the person who can be named a school director must posses appropriate education, competences, license and experience in education. Legal requirements allow the provision of effective training, but the fact that personal disposition can be both an advantage and an obstacle for acquiring necessary items of knowledge and skills, points to the necessity of including selection into the standard procedure for the election of a director. Democratization and decentralization of the educational system presupposes a series of structural, systemic and functional changes which reflect on school management and the role played by the director. This paper considers responsibilities and competences of directors, both in legislation and in school practice and addresses the question whether a school director is a manager or a leader, and what are the possibilities for the provision of professional resources for school management.
Keywords: directors; MANAGEMENT; school management; LEADERSHIP; management education